Roles of p38α mitogen‐activated protein kinase in mouse models of inflammatory diseases and cancer - Gupta, Jalaj; Nebreda, Angel R (The FEBS journal, 2015)
The p38α mitogen‐activated protein kinase pathway not only regulates the production of inflammatory mediators, but also controls processes related to tissue homeostasis, such as cell proliferation, differentiation and survival, which are often disrupted during malignant transformation. The versatility of this signaling pathway allows for the regulation of many specific functions depending on the cell type and context. Here, we discuss mouse models that have been used to identify in vivo functions of p38α signaling in the pathogenesis of inflammatory diseases and cancer. Experiments using genetically modified mice and pharmacological inhibitors support that targeting the p38α pathway could be therapeutically useful for some inflammatory diseases and tumor types.